The direct issuing fatwa on the distance between worshipers in congregational prayer in the Malaysian reality and the extent of its discipline concerning the consequences of actions and fatwa: mufti office of Kedah as an example - Ab Razak, Mohamed Rashid; Ismail, Abdul Manan (Academy of Contemporary Islamic Studies (ACIS), UiTM, 2022)
This research deals with the direct fatwa on the issue of spacing between worshipers in the congregational prayer and the extent of its discipline with respect to the outcome of actions and the consequences of the fatwa. The research is done through the use of the descriptive and analytical method to describe the essence of the topic and follow the opinions of the jurists regarding it and study it in the recognized references in Islamic jurisprudence, then come up with a reasonable and appropriate result. The researcher comes with directives and values from Islamic rulings and links them to the current Malaysian reality. The researcher also analyses the direct fatwa from Office of The Mufti Kedah in this regard, and the researcher concluded that this direct fatwa is complied with this discipline.